Respiratory diseases in young cattle - T. S. Ermilova; M. A. Samburova; O. V. Kasharnaya; E. A. O. Salimzade (Ветеринария сегодня)
The following review considers modern scientific data on respiratory diseases in young cattle. The problem of respiratory diseases in calves does not lose its relevance, since these pathologies rank second in frequency after diseases of the digestive system. In order to compile the data, the works of domestic and foreign researchers and collectives available in the collections of scientific conferences, seminars, symposiums, as well as in peer-reviewed periodicals, materials of dissertations and abstracts were reviewed. The group of pathologies under consideration is sufficiently diverse and can be caused by high animal density in the premises, overheating, hypothermia, unbalanced feeding, micronutrient deficiency, decreased body resistance, unfavorable epidemic situation and many other factors. However, out of the major calf diseases, particular mention should be made of pneumonia, which is most often caused by viruses. In this case agents can induce bacterial infection which aggravates and complicates the course of viral diseases. Microorganisms, such as Salmonella, Pasteurella and others, contribute to secondary infection and cause mixed forms of pneumonia. Bronchopneumonia is another disease covered in the article. It is a respiratory pathology characterized by inflammation of both the bronchi and lungs. As a rule, such disease types are most common in industrial animal husbandry, they are widespread and cause significant economic damage to the dairy and beef cattle breeding industries. The article pays great attention to these pathologies, justifies the importance of comprehensive preventive measures and timely diagnosis for livestock industries. To reduce the incidence of respiratory diseases in young cattle, it is necessary to strictly follow technological and hygienic standards for animal keeping and feeding. The use of combined medicines and preparations containing microelements increases treatment effectiveness.